Lead-tin mixed perovskite solar cell and preparation method thereof

By adding compounds of reducing oxygenamino acid groups to lead-tin mixed perovskite solar cells, the problem of poor efficiency and stability of lead-tin mixed perovskite solar cells is solved, and efficient and stable photoelectric conversion efficiency is achieved .

CN119486557APending Publication Date: 2025-02-18ADVANCED SOLAR TECH INST XUANCHENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411583177.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The efficiency and stability of lead-tin hybrid perovskite solar cells are limited by poor, limiting their commercialization process.

Method used

The compound with reducing oxygenamino acid groups is added to the lead-tin mixed perovskite layer to alleviate the oxidation and passivation-related defects of Sn2+, thereby improving the crystallization quality and stability of the perovskite film.

Benefits of technology

The photoelectric conversion efficiency and stability of lead-tin mixed perovskite solar cells are improved, with the photoelectric conversion efficiency up to 14.7%, and the initial value is maintained after 1,000 placement tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486557A_ABST
    Figure CN119486557A_ABST
Patent Text Reader

Abstract

The invention discloses a lead-tin mixed perovskite solar cell and a preparation method thereof, belongs to the technical field of lead-tin mixed perovskite solar cells, and overcomes the defects of poor efficiency and stability of lead-tin mixed perovskite in the prior art. The preparation method of the lead-tin mixed perovskite solar cell comprises the following steps: step 1, preparing a hole transport layer; 2, preparing a perovskite layer on the hole transport layer, wherein the perovskite layer comprises perovskite ABX3 and an additive; the additive is a compound containing a hydroxamic acid group; step 3, preparing an electron transport layer; 4, preparing a cathode modification layer; 5, preparing a metal electrode; the step 2 comprises: mixing an additive, CsBr and a second solvent to prepare an additive solution; in the additive solution, the concentration of the additive is greater than 0 and less than or equal to 0.1 mol / L.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-tin mixed perovskite solar cells, and in particular relates to a lead-tin mixed perovskite solar cell and a preparation method thereof. Background Art

[0002] Solar cell devices are devices that convert solar energy into electrical energy. In view of the increasingly severe energy problem, this is a very promising development direction. With the increase in the market share of photovoltaics, perovskite solar cells have developed rapidly due to their excellent photoelectric conversion efficiency, simple preparation method and low price cost.

[0003] At present, partial replacement of Pb with Sn in lead perovskite has been proven to be a very promising method. It can not only reduce environmental toxicity, but also lead-tin mixed perovskite solar cells have a band gap in the range of 1.1-1.4eV and a wide light absorption range of nearly 1000-1100nm. It is an ideal material that can make the efficiency of single-junction solar cells close to the Shockley-Quisser limit. It has been widely used and researched.

[0004] However, the efficiency and stability of lead-tin hybrid perovskite solar cells are poor, which limits their commercialization process. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of poor efficiency and stability of lead-tin mixed perovskite in the prior art, thereby providing a lead-tin mixed perovskite solar cell and a preparation method thereof.

[0006] To this end, the present invention provides the following technical solutions.

[0007] In a first aspect, the present invention provides a method for preparing a lead-tin mixed perovskite solar cell, comprising the following steps:

[0008] Step 1: preparing a hole transport layer on a transparent conductive substrate;

[0009] Step 2: Prepare a perovskite layer on the hole transport layer, the perovskite layer comprising perovskite ABX 3 and additives, wherein A includes Cs + 、MA + or FA + At least one of, B includes Pb 2+ and Sn 2+ , X includes F - , Cl - Br - or I - At least one of the following; the additive is a compound containing a hydroxamic acid group;

[0010] Step 3, preparing an electron transport layer on the lead-tin mixed perovskite layer;

[0011] Step 4, preparing a cathode modification layer on the electron transport layer;

[0012] Step 5, preparing a metal electrode on the cathode modification layer;

[0013] The step 2 comprises:

[0014] Preparation of ABX by using other than CsBr 3 The raw material is mixed with a first solvent to prepare a perovskite precursor solution;

[0015] The additive, CsBr and the second solvent are mixed to prepare an additive solution; in the additive solution, 0<the concentration of the additive≤0.1 mol / L;

[0016] The perovskite precursor solution is spin-coated on the hole transport layer, and the additive solution is added dropwise during the last 15-20 seconds of the spin-coating. After the spin-coating, annealing is performed to obtain a perovskite layer.

[0017] In one possible embodiment, 120-200 μl of the additive solution is added dropwise.

[0018] In a possible implementation, the additive includes one or more of p-butoxyphenylacetohydroxamic acid (AHA), acetohydroxamic acid and octanoylhydroxamic acid.

[0019] In one possible embodiment, the preparation of ABX other than CsBr 3 The raw materials include: cesium iodide (CsI), lead iodide (PbI 2 ), tin iodide (SnI 2 ), zinc iodide and stannous fluoride (SnF 2 );

[0020] Optionally, the molar ratio of cesium iodide, lead iodide, stannous iodide, zinc iodide, and stannous fluoride is 1:0.56:0.4:0.04:0.04;

[0021] In one possible embodiment, the first solvent consists of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF);

[0022] Optionally, the volume ratio of dimethyl sulfoxide (DMSO) to dimethylformamide (DMF) is (0.8-1):(3.2-3);

[0023] In a possible embodiment, the concentration of CsBr in the additive solution is 8 to 10 mg / ml;

[0024] In a possible implementation, the second solvent is isopropanol, methanol or ethanol.

[0025] In one possible embodiment, the spin coating speed of the perovskite precursor solution is 3500-4500 rpm, and the spin coating time is 55-65 s;

[0026] In a possible implementation manner, the annealing temperature in step 2 is 110-130° C., and the annealing time is 5 min-15 min.

[0027] In a possible implementation, step 1 includes:

[0028] Depositing a solution of hole transport layer material on the transparent conductive substrate and forming a hole transport layer after annealing;

[0029] Optionally, the hole transport layer material includes at least one of NiOx and PEDOT:PSS;

[0030] Optionally, the concentration of NiOx solution is 0.5-2.0 mg / mL;

[0031] Optionally, a solution of hole transport layer material is deposited on the transparent conductive substrate by spin coating;

[0032] Optionally, the annealing temperature in step 1 is 100 to 140° C., and the annealing time is 5 to 15 minutes;

[0033] Optionally, in step 1, the spin coating speed is 3500-4500 rpm, and the spin coating time is 55-65 s.

[0034] In a possible implementation, step 3 includes:

[0035] Mixing an electron transport layer material with a third solvent to prepare an electron transport layer solution, spin coating the electron transport layer solution on the perovskite layer, and annealing to obtain an electron transport layer;

[0036] Optionally, the electron transport layer material includes PCBM, BCP, C60 and SnO 2 One or more of;

[0037] Optionally, the concentration of the electron transport layer material in the electron transport layer solution is 20 to 30 mg / mL;

[0038] Optionally, the third solvent is chlorobenzene, isopropanol or methanol;

[0039] Optionally, the electron transport layer solution is spin-coated at a speed of 500 to 1500 rpm, and the spin-coating time is 35 to 45 s;

[0040] Optionally, the annealing temperature in step 3 is 55-65° C., and the annealing time is 5 min to 15 min.

[0041] In a possible implementation, step 4 includes:

[0042] Mixing a cathode modification layer material with a fourth solvent to prepare a cathode modification layer solution, and spin-coating the cathode modification layer solution on the electron transport layer;

[0043] Optionally, the cathode modification layer material is zirconium acetylacetonate (ZrAcac);

[0044] Optionally, the fourth solvent is ethanol, methanol or isopropanol;

[0045] Optionally, the concentration of the cathode modification layer material in the cathode modification layer solution is 0.5 to 1.5 mg / mL;

[0046] Optionally, the spin coating speed in step 4 is 4000-6000 rpm, and the spin coating time is 35-45 s.

[0047] In a possible implementation manner, the metal electrode is Ag, Cu or Au, and the electrode thickness is 100-140 nm.

[0048] In a second aspect, the present invention provides a lead-tin mixed perovskite solar cell, which is prepared by the preparation method of the lead-tin mixed perovskite solar cell.

[0049] The technical solution of the present invention has the following advantages:

[0050] 1. The preparation method of the lead-tin mixed perovskite solar cell of the present invention comprises the following steps: step 1, preparing a hole transport layer on a transparent conductive substrate; step 2, preparing a perovskite layer on the hole transport layer, the perovskite layer comprising perovskite ABX 3 and additives, wherein A includes Cs + 、MA + or FA + At least one of, B includes Pb 2+ and Sn 2+ , X includes F - , Cl - Br - or I - at least one of the following; the additive is a compound containing a hydroxamic acid group; step 3, preparing an electron transport layer on the lead-tin mixed perovskite layer; step 4, preparing a cathode modification layer on the electron transport layer; step 5, preparing a metal electrode on the cathode modification layer; the step 2 comprises: preparing ABX other than CsBr 3The raw material is mixed with a first solvent to obtain a perovskite precursor solution; an additive, CsBr and a second solvent are mixed to obtain an additive solution; in the additive solution, 0<the concentration of the additive≤0.1 mol / L; the perovskite precursor solution is spin-coated on the hole transport layer, the additive solution is added dropwise during the last 15-20 s of the spin-coating, and annealing is performed after the spin-coating to obtain a perovskite layer.

[0051] Due to Sn 2+ Very easy to be oxidized to Sn 4+ , and Sn-I antisite defects (SnI) are easily generated in a tin-rich environment. These defects will become non-radiative recombination centers on the surface and near-surface areas of the film, resulting in a significant loss of open circuit voltage (Voc), which will lead to poor photoelectric conversion efficiency and stability of the device. The present invention adds a compound having a reducing hydroxamic acid group (OC-NHOH) to the perovskite layer. The reducing hydroxamic acid group can not only alleviate the Sn 2+ The lead-tin mixed perovskite solar cell device has a photoelectric conversion efficiency of up to 14.7%, and after 1000 times of placement test, it still maintains more than 90% of the initial value. The lead-tin mixed perovskite solar cell prepared by the present invention has a high photoelectric conversion efficiency and good stability.

[0052] The preparation method of the present invention is simple, which is beneficial to ensuring device efficiency while making it have good device stability, and is convenient for large-scale manufacturing of high-efficiency lead-tin mixed perovskite solar cells and the development of stacked solar cells made based on lead-tin mixed perovskite. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0054] Figure 1 The stability test results of Example 2, Comparative Example 1 and Comparative Example 2 are shown. DETAILED DESCRIPTION

[0055] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0056] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0057] Example 1

[0058] This embodiment provides a method for preparing a lead-tin mixed perovskite solar cell, comprising the following steps:

[0059] (1) First, the front and back sides of the 2.5 cm*2.5 cm FTO transparent conductive substrate were cleaned with glass cleaning agent, and then ultrasonically cleaned with ultrapure water, isopropyl alcohol and anhydrous ethanol for 15 minutes each in sequence, and then dried in an oven at 60°C, and then pretreated with ozone for 15 minutes.

[0060] (2) Preparation of a hole transport layer on a FTO transparent conductive substrate: 120 μl of a 0.5 mg / mL NiOx aqueous solution was dripped onto the FTO transparent conductive substrate, spin coated at 4000 rpm for 30 s, and annealed at 100°C for 10 min.

[0061] (3) Preparation of perovskite layer:

[0062] Cesium iodide (CsI), lead iodide (PbI 2 ), tin iodide (SnI 2 ), zinc iodide, stannous fluoride (SnF 2 ) was dissolved in a mixed solvent (the mixed solvent consisted of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) in a volume ratio of 1:3), stirred at 50°C for 2 hours until uniform, and a perovskite precursor solution was obtained. The concentration of CsI in the perovskite precursor solution was 1 mol / L, and PbI 2 The concentration is 0.56 mol / L, SnI 2 The concentration is 0.4 mol / L, the concentration of zinc iodide is 0.04 mol / L, SnF 2 The concentration is 0.04mol / L.

[0063] The additive of p-butyloxyphenylacetohydroxamic acid was added to a 10 mg / mL isopropanol solution of CsBr to prepare an additive solution with an additive concentration of 0.02 mol / L.

[0064] 120 μL of perovskite precursor solution was dropped onto the hole transport layer and spin coated at 4000 rpm for 60 s. After 40 s, 200 μL of additive solution was added and annealed at 120°C for 10 min.

[0065] (4) Preparation of electron transport layer:

[0066] PCBM and chlorobenzene were mixed to prepare an electron transport layer solution with a concentration of 25 mg / ml. 60 μl of the electron transport layer solution was dropped onto the perovskite layer, spin-coated at a speed of 1000 rpm for 40 s, and annealed at 60° C. for 5 min.

[0067] (5) Preparation of cathode modification layer:

[0068] ZrAcac was mixed with ethanol to prepare a cathode modification layer solution with a concentration of 1.0 mg / mL, and then 60 μl of the cathode modification layer solution was dropped onto the electron transport layer and spin-coated at a rotation speed of 5000 rpm for 40 s.

[0069] (6) Preparation of metal electrode: A metal electrode Ag with a thickness of 120 nm was prepared on the cathode modification layer by an evaporation method.

[0070] Under AM1.5G simulated sunlight, the lead-tin mixed perovskite solar cell device prepared in this embodiment has a PCE of 13.7%, a Voc of 0.76V, and a Jsc of 24.3mA / cm 2 , FF is 74.2%.

[0071] Example 2

[0072] This embodiment provides a method for preparing a lead-tin mixed perovskite solar cell, comprising the following steps:

[0073] (1) First, the front and back sides of the 2.5 cm*2.5 cm FTO transparent conductive substrate were cleaned with glass cleaning agent, and then ultrasonically cleaned with ultrapure water, isopropyl alcohol and anhydrous ethanol for 15 minutes each in sequence, and then dried in an oven at 60°C, and then pretreated with ozone for 15 minutes.

[0074] (2) Preparation of a hole transport layer on a FTO transparent conductive substrate: 120 μl of a 0.5 mg / mL NiOx aqueous solution was dripped onto the FTO transparent conductive substrate, spin coated at 4000 rpm for 30 s, and annealed at 100°C for 10 min.

[0075] (3) Preparation of perovskite layer:

[0076] Cesium iodide (CsI), lead iodide (PbI 2 ), tin iodide (SnI 2), zinc iodide, stannous fluoride (SnF 2 ) was dissolved in a mixed solvent (the mixed solvent consisted of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) in a volume ratio of 1:3), stirred at 50°C for 2 hours until uniform, and a perovskite precursor solution was obtained. The concentration of CsI in the perovskite precursor solution was 1 mol / L, and PbI 2 The concentration is 0.56 mol / L, SnI 2 The concentration is 0.4 mol / L, the concentration of zinc iodide is 0.04 mol / L, SnF 2 The concentration is 0.04mol / L.

[0077] The additive of p-butyloxyphenylacetohydroxamic acid was added to a 10 mg / mL isopropanol solution of CsBr to prepare an additive solution with an additive concentration of 0.04 mol / L.

[0078] 120 μL of perovskite precursor solution was dropped onto the hole transport layer and spin coated at 4000 rpm for 60 s. After 40 s, 200 μL of additive solution was added and annealed at 120°C for 10 min.

[0079] (4) Preparation of electron transport layer:

[0080] PCBM and chlorobenzene were mixed to prepare an electron transport layer solution with a concentration of 25 mg / ml. 60 μl of the electron transport layer solution was dropped onto the perovskite layer, spin-coated at a speed of 1000 rpm for 40 s, and annealed at 60° C. for 5 min.

[0081] (5) Preparation of cathode modification layer:

[0082] ZrAcac was mixed with ethanol to prepare a cathode modification layer solution with a concentration of 1.0 mg / mL, and then 60 μl of the cathode modification layer solution was dropped onto the electron transport layer and spin-coated at a rotation speed of 5000 rpm for 40 s.

[0083] (6) Preparation of metal electrode: A metal electrode Ag with a thickness of 120 nm was prepared on the cathode modification layer by an evaporation method.

[0084] Under AM1.5G simulated sunlight, the lead-tin mixed perovskite solar cell device prepared in this embodiment has a PCE of 14.7%, a Voc of 0.78V, and a Jsc of 25.3mA / cm 2 , FF is 74.3%.

[0085] Example 3

[0086] This embodiment provides a method for preparing a lead-tin mixed perovskite solar cell, comprising the following steps:

[0087] (1) First, the front and back sides of the 2.5 cm*2.5 cm FTO transparent conductive substrate were cleaned with glass cleaning agent, and then ultrasonically cleaned with ultrapure water, isopropyl alcohol and anhydrous ethanol for 15 minutes each in sequence, and then dried in an oven at 60°C, and then pretreated with ozone for 15 minutes.

[0088] (2) Preparation of a hole transport layer on a FTO transparent conductive substrate: 120 μl of a 0.5 mg / mL NiOx aqueous solution was dripped onto the FTO transparent conductive substrate, spin coated at 4000 rpm for 30 s, and annealed at 100°C for 10 min.

[0089] (3) Preparation of perovskite layer:

[0090] Cesium iodide (CsI), lead iodide (PbI 2 ), tin iodide (SnI 2 ), zinc iodide, stannous fluoride (SnF 2 ) was dissolved in a mixed solvent (the mixed solvent consisted of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) in a volume ratio of 1:3), stirred at 50°C for 2 hours until uniform, and a perovskite precursor solution was obtained. The concentration of CsI in the perovskite precursor solution was 1 mol / L, and PbI 2 The concentration is 0.56 mol / L, SnI 2 The concentration is 0.4 mol / L, the concentration of zinc iodide is 0.04 mol / L, SnF 2 The concentration is 0.04mol / L.

[0091] The additive of p-butyloxyphenylacetohydroxamic acid was added to a 10 mg / mL isopropanol solution of CsBr to prepare a 0.06 mol / L additive solution.

[0092] 120 μL of perovskite precursor solution was dropped onto the hole transport layer and spin coated at 4000 rpm for 60 s. After 40 s, 200 μL of additive solution was added and annealed at 120°C for 10 min.

[0093] (4) Preparation of electron transport layer:

[0094] PCBM and chlorobenzene were mixed to prepare an electron transport layer solution with a concentration of 25 mg / ml. 60 μl of the electron transport layer solution was dropped onto the perovskite layer, spin-coated at a speed of 1000 rpm for 40 s, and annealed at 60° C. for 5 min.

[0095] (5) Preparation of cathode modification layer:

[0096] ZrAcac was mixed with ethanol to prepare a cathode modification layer solution with a concentration of 1.0 mg / mL, and then 60 μl of the cathode modification layer solution was dropped onto the electron transport layer and spin-coated at a rotation speed of 5000 rpm for 40 s.

[0097] (6) Preparation of metal electrode: A metal electrode Ag with a thickness of 120 nm was prepared on the cathode modification layer by an evaporation method.

[0098] Under AM1.5G simulated sunlight, the lead-tin mixed perovskite solar cell device prepared in this embodiment has a PCE of 13.4%, a Voc of 0.75V, and a Jsc of 24.1mA / cm 2 , FF is 74%.

[0099] Example 4

[0100] This embodiment provides a method for preparing a lead-tin mixed perovskite solar cell, comprising the following steps:

[0101] (1) First, the front and back sides of the 2.5 cm*2.5 cm FTO transparent conductive substrate were cleaned with glass cleaning agent, and then ultrasonically cleaned with ultrapure water, isopropyl alcohol and anhydrous ethanol for 15 minutes each in sequence, and then dried in an oven at 60°C, and then pretreated with ozone for 15 minutes.

[0102] (2) Preparation of a hole transport layer on a FTO transparent conductive substrate: 120 μl of a 2.0 mg / mL PEDOT:PSS aqueous solution was dripped onto a FTO transparent conductive substrate, spin coated at 3000 rpm for 35 s, and annealed at 110° C. for 15 min.

[0103] (3) Preparation of perovskite layer:

[0104] Cesium iodide (CsI), lead iodide (PbI 2 ), tin iodide (SnI 2 ), zinc iodide, stannous fluoride (SnF 2 ) was dissolved in a mixed solvent (the mixed solvent consisted of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) in a volume ratio of 1:3), stirred at 50°C for 2 hours until uniform, and a perovskite precursor solution was obtained. The concentration of CsI in the perovskite precursor solution was 1 mol / L, and PbI 2 The concentration is 0.56 mol / L, SnI 2 The concentration is 0.4 mol / L, the concentration of zinc iodide is 0.04 mol / L, SnF 2 The concentration is 0.04mol / L.

[0105] The acetohydroxamic acid additive was added to a 10 mg / mL CsBr isopropanol solution to prepare a 0.04 mol / L additive solution.

[0106] 120 μL of perovskite precursor solution was dropped onto the hole transport layer and spin coated at 4000 rpm for 60 s. After 40 s, 200 μL of additive solution was added and annealed at 120°C for 10 min.

[0107] (4) Preparation of electron transport layer:

[0108] BCP and chlorobenzene were mixed to prepare an electron transport layer solution with a concentration of 25 mg / ml. 60 μl of the electron transport layer solution was dropped onto the perovskite layer, spin-coated at a speed of 1500 rpm for 35 s, and annealed at 80° C. for 10 min.

[0109] (5) Preparation of cathode modification layer:

[0110] ZrAcac was mixed with methanol to prepare a cathode modification layer solution with a concentration of 1.0 mg / mL, and then 80 μl of the cathode modification layer solution was dropped onto the electron transport layer and spin-coated at a rotation speed of 4500 rpm for 30 s.

[0111] (6) Preparation of metal electrode: A metal electrode Ag with a thickness of 100 nm was prepared on the cathode modification layer by an evaporation method.

[0112] Under AM1.5G simulated sunlight, the lead-tin mixed perovskite solar cell device prepared in this embodiment has a PCE of 13.6%, a Voc of 0.75V, and a Jsc of 24.8mA / cm 2 , FF is 73.2%.

[0113] Example 5

[0114] This embodiment provides a method for preparing a lead-tin mixed perovskite solar cell, comprising the following steps:

[0115] (1) First, the front and back sides of the 2.5 cm*2.5 cm FTO transparent conductive substrate were cleaned with glass cleaning agent, and then ultrasonically cleaned with ultrapure water, isopropyl alcohol and anhydrous ethanol for 15 minutes each in sequence, and then dried in an oven at 60°C, and then pretreated with ozone for 15 minutes.

[0116] (2) Preparation of a hole transport layer on a FTO transparent conductive substrate: 120 μl of a 2.0 mg / mL PEDOT:PSS aqueous solution was dripped onto a FTO transparent conductive substrate, spin coated at 3000 rpm for 35 s, and annealed at 110° C. for 15 min.

[0117] (3) Preparation of perovskite layer:

[0118] Cesium iodide (CsI), lead iodide (PbI 2 ), tin iodide (SnI 2 ), zinc iodide, stannous fluoride (SnF 2 ) was dissolved in a mixed solvent (the mixed solvent consisted of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) in a volume ratio of 1:3), stirred at 50°C for 2 hours until uniform, and a perovskite precursor solution was obtained. The concentration of CsI in the perovskite precursor solution was 1 mol / L, and PbI 2 The concentration is 0.56 mol / L, SnI 2 The concentration is 0.4 mol / L, the concentration of zinc iodide is 0.04 mol / L, SnF 2 The concentration is 0.04mol / L.

[0119] The octanoyl hydroxamic acid additive was added to a 10 mg / mL CsBr isopropanol solution to prepare a 0.04 mol / L additive solution.

[0120] 120 μL of perovskite precursor solution was dropped onto the hole transport layer and spin coated at 4000 rpm for 60 s. After 40 s, 200 μL of additive solution was added and annealed at 120°C for 10 min.

[0121] (4) Preparation of electron transport layer:

[0122] BCP and chlorobenzene were mixed to prepare an electron transport layer solution with a concentration of 25 mg / ml. 60 μl of the electron transport layer solution was dropped onto the perovskite layer, spin-coated at a speed of 1500 rpm for 35 s, and annealed at 80° C. for 10 min.

[0123] (5) Preparation of cathode modification layer:

[0124] ZrAcac was mixed with methanol to prepare a cathode modification layer solution with a concentration of 1.0 mg / mL, and then 80 μl of the cathode modification layer solution was dropped onto the electron transport layer and spin-coated at a rotation speed of 4500 rpm for 30 s.

[0125] (6) Preparation of metal electrode: A metal electrode Ag with a thickness of 100 nm was prepared on the cathode modification layer by an evaporation method.

[0126] Under AM1.5G simulated sunlight, the lead-tin mixed perovskite solar cell device prepared in this embodiment has a PCE of 13.0%, a Voc of 0.74V, and a Jsc of 24.2mA / cm 2 , FF is 73%.

[0127] Comparative Example 1

[0128] This comparative example is substantially the same as Example 1, except that in step (3), no p-butyloxyphenylacetylhydroxamic acid is added to the isopropanol solution of CsBr.

[0129] Under AM1.5G simulated sunlight, the lead-tin mixed perovskite solar cell device prepared in this embodiment has a PCE of 12.7%, a Voc of 0.72V, and a Jsc of 24.3mA / cm 2 , FF is 72.5%.

[0130] Comparative Example 2

[0131] This comparative example is substantially the same as Example 1, except that the concentration of p-butyloxyphenylacetylhydroxamic acid in the additive solution in step (3) is 0.2 mol / L.

[0132] Under AM1.5G simulated sunlight, the lead-tin mixed perovskite solar cell device prepared in this embodiment has a PCE of 10.7%, a Voc of 0.68V, and a Jsc of 22.5mA / cm 2 , FF is 70.2%.

[0133] Table 1 Performance of lead-tin mixed perovskite solar cells

[0134] PCE(%) Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) Example 1 13.7 0.76 24.3 74.2 Example 2 14.7 0.78 25.3 74.3 Example 3 13.4 0.75 24.1 74.0 Example 4 13.6 0.75 24.8 73.2 Example 5 13.0 0.74 24.2 73.0 Comparative Example 1 12.7 0.72 24.3 72.5 Comparative Example 2 10.7 0.68 22.5 70.2

[0135] It can be seen from Table 1 that the solar cell of the present invention has a relatively high photoelectric conversion efficiency.

[0136] Stability performance test method: Continuously monitor device performance at an ambient humidity of 85% and a temperature of 85°C, perform an IV test every 2s, and test 1000 times. The test results are shown in Figure 1 .Depend on Figure 1 It can be seen that the solar cell of the present invention has higher stability.

[0137] Test results see Figure 1 ,Depend on Figure 1 It can be seen that when the additive is p-butyloxyphenylacetohydroxamic acid and the concentration of the additive in the additive solution is 0.04 mol / L, the device has the best performance.

[0138] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a lead-tin mixed perovskite solar cell, characterized in that: The following steps are involved: Step 1: preparing a hole transport layer on a transparent conductive substrate; Step 2: Prepare a perovskite layer on the hole transport layer, wherein the perovskite layer includes perovskite ABX3 and additives, wherein A includes Cs + 、MA + or FA + At least one of B including Pb 2+ and Sn 2+ , X includes F - , Cl - Br - or I - At least one of the following; the additive is a compound containing a hydroxamic acid group; Step 3, preparing an electron transport layer on the lead-tin mixed perovskite layer; Step 4, preparing a cathode modification layer on the electron transport layer; Step 5, preparing a metal electrode on the cathode modification layer; The step 2 comprises: Mixing the raw materials for preparing ABX3 except CsBr with the first solvent to prepare a perovskite precursor solution; The additive, CsBr and the second solvent are mixed to prepare an additive solution; in the additive solution, 0<the concentration of the additive≤0.1 mol / L; The perovskite precursor solution is spin-coated on the hole transport layer, and the additive solution is added dropwise during the last 15-20 seconds of the spin-coating. After the spin-coating, annealing is performed to obtain a perovskite layer.

2. The method for preparing a lead-tin mixed perovskite solar cell according to claim 1, characterized in that: Raw materials other than CsBr for preparing ABX3 include CsI, PbI2, SnI2, ZnI2 and SnF2.

3. The method for preparing a lead-tin mixed perovskite solar cell according to claim 2, characterized in that: In the step of adding the additive solution dropwise during the last 15-20 s of the spin coating, 120-200 μl of the additive solution was added dropwise.

4. The method for preparing a lead-tin mixed perovskite solar cell according to claim 2 or 3, characterized in that: The additive includes one or more of p-butyloxyphenylacetohydroxamic acid, acetohydroxamic acid and octanoylhydroxamic acid.

5. The method for preparing a lead-tin mixed perovskite solar cell according to claim 2 or 3, characterized in that: The concentration of CsBr in the additive solution is 8-10 mg / ml.

6. The method for preparing a lead-tin mixed perovskite solar cell according to claim 2 or 3, characterized in that: The step 2 satisfies at least one of the following conditions: (1) The spin coating speed of the perovskite precursor solution is 3500-4500 rpm, and the spin coating time is 55-65 s; (2) The annealing temperature in step 2 is 110-130° C., and the annealing time is 5 min-15 min.

7. The method for preparing a lead-tin mixed perovskite solar cell according to claim 1 or 2, characterized in that: The step 1 comprises: Depositing a solution of hole transport layer material on the transparent conductive substrate, and forming a hole transport layer after annealing; optionally, the annealing temperature in step 1 is 100 to 140° C., and the annealing time is 5 min to 15 min; Optionally, in step 1, the spin coating speed is 3500-4500 rpm, and the spin coating time is 55-65 s.

8. The method for preparing a lead-tin mixed perovskite solar cell according to any one of claims 1 to 3, characterized in that: The step 3 comprises: mixing the electron transport layer material with a third solvent to prepare an electron transport layer solution, spin coating the electron transport layer solution on the perovskite layer, and annealing to obtain the electron transport layer; Optionally, the electron transport layer material includes one or more of PCBM, BCP, C60 and SnO2; Optionally, the concentration of the electron transport layer material in the electron transport layer solution is 20 to 30 mg / mL; Optionally, the electron transport layer solution is spin-coated at a speed of 500 to 1500 rpm, and the spin-coating time is 35 to 45 s; Optionally, the annealing temperature in step 3 is 55-65° C., and the annealing time is 5 min to 15 min.

9. The method for preparing a lead-tin mixed perovskite solar cell according to any one of claims 1 to 3, characterized in that: The step 4 comprises: mixing the cathode modification layer material with a fourth solvent to prepare a cathode modification layer solution, and spin coating the cathode modification layer solution on the electron transport layer; Optionally, the cathode modification layer material is zirconium acetylacetonate; Optionally, the fourth solvent is ethanol, methanol or isopropanol; Optionally, the concentration of the cathode modification layer material in the cathode modification layer solution is 0.5 to 1.5 mg / mL; Optionally, the spin coating speed in step 4 is 4000-6000 rpm, and the spin coating time is 35-45 s; Optionally, the metal electrode is Ag, Cu or Au, and the electrode thickness is 100 to 140 nm.

10. A lead-tin mixed perovskite solar cell, characterized in that: The lead-tin mixed perovskite solar cell is prepared by the preparation method of any one of claims 1 to 9.